The interaction of compositional and performing means of expressiveness in the Second Sonata-Ballade by Boris Lyatoshinsky - Bezborodko, Oleg (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
Relevance of the study. Despite the division of the spheres of compositional and performing musical creativity the traditional generally accepted distinction between compositional and performing means of expressiveness is recognized by many researchers as ambiguous and conditional. The unprecedented actualization of the "secondary" performing means of expressiveness in the musical art of the twentieth century stipulates the urgency of applying this aspect of research to the study of the early piano pieces by the leading Ukrainian composer of the twentieth century Boris Lyatoshinsky. Main objective of the study is to highlight the interaction of compositional and performing means of expressiveness in the Second Sonata-Ballade by B. Lyatoshinsky. Methodology. A holistic musical-theoretical analysis is applied to determine the figurative content of a work, to reveal the features of form-building and the use of compositional means of expressiveness (the intonational structure of the basic elements of the form, the tonal-harmonic plan, the methods of development of the thematic material). Complex interpretation analysis is applied to study how performing means of expressiveness (tempo-rhythm, agogics, pedalization, dynamics) are used in their interaction with composer means of expressiveness. Results and conclusions. In this work, the composer counts on the significant co-creative role of the interpreter. So, the definition of the tempo plan of the work is essential for the perception of the form, which ambivalence is evident already from the title of the work. A significant degree of metrorhythmic freedom is expected with accurate observance of rhythmic figures of a nervous, impulsive nature. It is necessary to use special dynamic and pedal techniques to identify impressionistic features of the B. Lyatoshinsky’s piano texture. Practical significance. The thourough understanding of the dialectics of interaction between compositional and performing means of expressiveness is necessary in order to achieve an adequate and convincing interpretation of this outstanding work of Ukrainian piano music.